Glioblastoma Cells Express and Secrete Alternatively Spliced Transcripts of Coagulation Factor X - Xiaotian Li; Xilei Liu; Yalong Gao; Lei Li; Yajuan Wang; Jianlong Men; Jing Ren; Jiwei Wang; Fanjian Li; Yaohua Li; Jianhua Xiong; Xiaoteng Cui; et al. (Biomedicines)
Background: Patients with cancer often develop a prothrombotic state that can evolve into venous and arterial thrombosis, which is associated with poor clinical outcomes. Glioblastoma multiforme (GBM) is the most frequently associated with thrombosis, but the underlying causes of this prothrombotic state are poorly defined. Objectives: We designed a study to characterize the expression of coagulation factor X (FX) and its alternatively spliced transcripts in glioblastoma tissues surgically removed from patients and in clonal cell lines. Methods: The F10 mRNA and FX protein were quantified in tissues surgically removed from seven patients with glioblastoma (glioma grade 3–4) and those from non-tumor patients. Glioblastoma cells from three human clonal lines were examined for the expression and secretion of FX at baseline and after the cells were stimulated with lipopolysaccharide (LPS) or subjected to oxygen/glucose starvation in culture. PCR products were subjected to Sanger sequencing and amplicon sequencing to identify F10 isoforms and their ratios. A chromogenic assay was performed to assess FX activity. Results: Glioblastoma tissue and cell lines expressed high levels of the full-length and an alternatively spliced F10 mRNA. The latter produced a C-terminal truncated FX. The ratio of full-length to truncated F10 transcripts was significantly higher in normal brain tissues than in glioblastoma tissue. In cultured cells from the glioblastoma cell lines, FX was secreted to the conditioned medium and was active in cleaving a chemical substrate. The FX expression and secretion were upregulated in cells stimulated with LPS or subjected to oxygen/glucose starvation. Discussion: Glioblastoma cells synthesize and secrete FX that was active in promoting thrombin generation. These findings provide a new underlying mechanism to explain why glioblastoma patients are prone to developing thrombosis.